Limits on fast radio bursts at 145 MHz with ARTEMIS, a real-time software backend - Karastergiou, A; Chennamangalam, J; Armour, W; Williams, C; Mort, B; Dulwich, F; Salvini, S; Magro, A; Roberts, S; Serylak, M; Doo, A; Bilous, A; et al. (Oxford University Press, 2015)
Fast Radio Bursts (FRBs), are millisecond radio signals that exhibit dispersion larger than what the Galactic electron density can account for. We have conducted a 1446 hour survey for Fast Radio Bursts (FRBs) at 145 MHz, covering a total of 4193 sq. deg on the sky. We used the UK station of the LOFAR radio telescope – the Rawlings Array – , accompanied for a majority of the time by the LOFAR station at Nançay, observing the same fields at the same frequency. Our real-time search backend, ARTEMIS, utilizes graphics processing units to search for pulses with dispersion measures up to 320 cm^-3 pc. Previous derived FRB rates from surveys around 1.4 GHz, and favoured FRB interpretations, motivated this survey, despite all previous detections occurring at higher dispersion measures. We detected no new FRBs above a signal-to-noise threshold of 10, leading to the most stringent upper limit yet on the FRB event rate at these frequencies: 29 sky^-1 day^-1 for 5 ms-duration pulses above 62 Jy. The non-detection could be due to scatter-broadening, limitations on the volume and time searched, or the shape of FRB flux density spectra. Assuming the latter and that FRBs are standard candles, the non-detection is compatible with the published FRB sky rate, if their spectra follow a power law with frequency (∝ v^α), with α ≳ +0.1, demonstrating a marked difference from pulsar spectra. Our results suggest that surveys at higher frequencies, including the low frequency component of the Square Kilometre Array, will have better chances to detect, estimate rates and understand the origin and properties of FRBs.